Secondary antibiotic resistance of Helicobacter pylori isolates in Israeli children and adults. (September 2017) - Khoury, Johad; Geffen, Yuval; Shaul, Ron; Sholy, Hisham; Chowers, Yehuda; Saadi, Tarek
Highlights: The sensitivity of H. pylori culture is as low as 74%. Resistance of H. pylori to metronidazole and clarithromycin is very high after failure of two therapeutic. No levofloxacin resistance was detected in children. Amoxicillin resistance is higher in adults than in children. Abstract: Background: Failure of standard therapy for Helicobacter pylori infections results primarily from increasing antibiotic resistance. Patients in Israel are referred for H. pylori culture after failure of at least two therapeutic regimens. Objectives: To estimate the prevalence of secondary antimicrobial resistance of H. pylori in Israel. Methods: We retrospectively collected results of H. pylori cultures performed by gastric biopsies at Rambam Health Care Campus, Haifa, Israel, between the years 2012-2015. Antimicrobial susceptibility to five drugs was tested by gradient-diffusion. Results: 107 patients, 46 adults and 61 children, were referred for performance of H. pylori cultures. Cultures were positive in 64 samples (63.7%). In adults, 23 (50%) patients had positive H. pylori cultures; 8.69% showed resistance to amoxicillin (AM), 39.1% to clarithromycin (CH), 61.9% to metronidazole (MZ), 8.69% to tetracycline (TC), and 21.7% to levofloxacin (LEV). In children, 41 (67%) patients had positive H. pylori cultures; 5.1% showed resistance to AM, 42.5% to CH, 46.66% to MZ, 2.5% to TC and 0% to LEV. In children, 94.9% of H. pylori strains were susceptible to both AM and LEV. In adults, 82.6% of the strains were susceptible to both AM and TC. 28.6% of adults and 24.1% children were resistant to both MZ and CH. Conclusions: The sensitivity of H. pylori culture was low. Resistance of H. pylori to MZ and CH was very high after failure of two therapeutic regimens in both adults and children. No LEV resistance was detected in children. AM resistance was higher in adults than in children.